The Role of Parental Capacity for Medical Decision-Making in Medical Ethics and the Care of Psychiatrically Ill Youth: Case Report - Bieber, Ewa D.; Edelsohn, Gail A.; McGee, Maria E.; Shekunov, Julia; Romanowicz, Magdalena; Vande Voort, Jennifer L.; McKean, Alastair J. S. (Frontiers in Psychiatry, 2020)
Introduction: Parents/legal guardians are medical decision-makers for their minor children. Lack of parental capacity to appreciate the implications of the diagnosis and consequences of refusing recommended treatment may impede pediatric patients from receiving adequate medical care. Child and adolescent psychiatrists (CAPs) need to appreciate the ethical considerations relevant to overriding parental medical decision-making when faced with concerns for medical neglect. Methods: Two de-identified cases illustrate the challenges inherent in clinical and ethical decision-making reflected in concerns for parental capacity for medical decision-making. Key ethical principles are reviewed. Case 1: Treatment of an adolescent with an eating disorder ethically complex due to the legal guardian’s inability to adhere with treatment recommendations leading to the patient’s recurrent abrupt weight loss. Case 2: Questions of parental decisional capacity amid treatment of an adolescent with schizoaffective disorder raised due to parental mistrust of diagnosis, disagreement with treatment recommendations, and lack of appreciation of the medical severity of the situation with repeated discharges against medical advice and medication nonadherence. Discussion: Decisions to question parental capacity for medical decision-making when risk of imminent harm is low but concern for medical neglect exists are controversial. Systematic review of cases concerning for medical neglect benefits from the assessment of parental decisional capacity, review of ethical standards and principles. Conclusion: Recognition of the importance of parental decision-making capacity as relates to parental autonomy and medical neglect and understanding key ethical principles will enhance the CAP’s capacity in medical decision-making when stakes are high and absolute recommendations are lacking.